Crime under the Light? Examining the Effects of Nighttime Lighting on Crime in China - Chong Peng; Weizeng Sun; Xi Zhang (Land, 2022)
With Chinese people’s increasing willingness to participate in night activities, local governments have begun regarding the nighttime economy as an important means to stimulate urban vitality and increase social employment. This study uses changes in urban nighttime light brightness as a measure of environmental factors to examine the social effects of nighttime activities. Based on panel data for 227 prefecture-level cities in China from 2000 to 2013, this study empirically investigates the effect and mechanism of nighttime light brightness on the urban crime rate. Empirical results show that (1) a 1% increase in nighttime light brightness increases criminal arrest rate and prosecution rate by 1.474% and 2.371%, respectively; (2) the effects are larger in developed areas with higher levels of lighting and economic development, or in urban areas (compared with rural areas), and (3) the mechanism test shows that such effects are more pronounced in cities with more nighttime business, confirming the existence of a crime opportunity effect.